Learning flexibility and environmental changes with the advent of online learning during COVID-19 pandemic / Nik Sarina Nik Md Salleh ... [et al.] - Nik Md Salleh, Nik Sarina; Hamid, Roseliza; Abdul Rahman, Khadijah; Zainal Abidin, Iffah Farzana; Zawawi, Amirah Syarwarshah (Universiti Teknologi MARA, Perlis, 2022)
The vital purpose of this study is to identify whether learning flexibility and environment will influence undergraduate students’ online learning during the COVID-19 pandemic in Malaysia. It is important to point out the determinants that will influence online learning that needs to be faced despite experiencing this world health crisis. The high level of online learning among students will also improve the performance of educational institutions which need to be competitive with other competitors in the sector. In addition, this study also aims to measure whether gender has a significant difference in undergraduates’ online learning. Thus, survey questions from previous studies were adopted and customised to collect data. A sample of 129 undergraduate students from one UiTM branch campus who have experienced online learning in the previous semester in the year 2021. The results of this study indicate that there are significant relationships between learning flexibility, environment and online learning. The findings also reveal that the level of online learning among undergraduate students is moderate. Moreover, it is confirmed that gender has a significant difference in online learning outcomes among students. For future research, the use of more quizzes that can stimulate understanding of learning delivered online needs to be emphasized by knowledge communicators in this revolution of the learning process.